GE_GERICHTE P/13640/2020 vom 30. August 2023 - GE Cour de justice (2023)
INJURE;DÉNONCIATION CALOMNIEUSE;LÉSION CORPORELLE;VOIES DE FAIT;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) | CP.319; CP.123; CP.126; CP.144; CP.177; CP.303